Maytag : takeover strategies - Raviv, Artur; Feuer, Rod N.; Mehrotra, Parth; Rossmann, Peter (London : SAGE Publications Ltd, 2017)
On April 22, 2005, Maytag Corporations stock price fell 28 percent after the company reported disappointing first-quarter results and significantly reduced its earnings outlook for 2005. The company's sales were declining due to increased foreign competition and its production costs were increasing due to higher energy, materials, and distribution costs. Maytags management and board clearly understood the need to make strategic decisions to turn around the fate of their company. Maytag could propose a drastic turnaround plan and remain independent, sell itself to either a large domestic competitor such as Whirlpool or a foreign firm such as Haier, or it could choose to go private by selling to a financial buyer (Ripplewood).
Originally published in Raviv, A., Feuer, R., Mehrota, P., & Rossman, P. (2008). Maytag: Takeover strategies. 5-208-258. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Maytag Corporation; Corporate turnarounds; Consolidation and merger of corporations